ESTIMATION OF ENDOSCOPIC SYNUSOTHOMY EFFICIENCY IN CHRONIC RHINOSINUSITIS WITH NASAL POLYPS BASED ON DATA OF ENT CLINIC OF PUBLIC INSTITUTION «NATIONAL MEDICAL CENTER» OF THE REPUBLIC OF TAJIKISTAN - М.К. IKROMOV; D.SH. DAVLATOV; М.B. NAZIRMADOVA; А.А. ABDUKHALILOV (Avicenna Tajik State Medical University, 2017)
Objective: To conduct a comparative analysis of the effectiveness of endoscopic and traditional surgeries in patients with chronic rhinosinusitis with nasal polyps. Methods: At the age of 21 to 65 years, 56 of patients with chronic rhinosinusitis with nasal polyps were diagnosed. Patients were divided into two groups: 1st group (31 patients - the main group), in which surgical interventions were performed endoscopically and 2nd group (25 patients - control group), in which patients underwent surgery using traditional methods. Results: The effectiveness of the method was estimated based on the relapse frequency of the patients who underwent surgery. Analysis of the long-term results showed that relapse of the disease was detected in 12.9% of the patients of the main group and 40% of the control group. Conclusion: The method of endonasal endoscopic rhinosinusotomy in chronic rhinosinusitis with nasal polyps proved to be more effective than traditional method of treatment.